Factor analysis of the banks' deposit policy - Sakibaeva, K. S. (Journal of Economic Research & Business Administration, 2016)
As you know, the primary source of resources second-tier banks in Kazakhstan are deposits. Therefore, the formation of the deposit policy is necessary to know the methods and means of attracting investors. To do this, first of all in determining the degree of influence of the factors important to factor analysis. Types of deposits offered to the public and a lot of tough price competition between banks. This article examines some of the factors that may affect the bank's deposit policy: minimum reserve requirements, the exchange rate, changes in population growth, the rate of refinancing, the average income of the population. The approach used in the research is combined character. Built econometric model allows us to estimate the degree of influence of each factor on the demand deposit services.